2013
DOI: 10.1093/brain/awt139
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking and disability progression in multiple sclerosis: United Kingdom cohort study

Abstract: Tobacco smoking has been linked to an increased risk of multiple sclerosis. However, to date, results from the few studies on the impact of smoking on the progression of disability are conflicting. The aim of this study was to investigate the effects of smoking on disability progression and disease severity in a cohort of patients with clinically definite multiple sclerosis. We analysed data from 895 patients (270 male, 625 female), mean age 49 years with mean disease duration 17 years. Forty-nine per cent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 47 publications
6
128
3
1
Order By: Relevance
“…Like other autoimmune disorders, MS is considered to be triggered by environmental factors in individuals with a genetic predisposition, and smoking has been considered one of the most established environmental risk factors for this illness (Mandia et al., 2014; Ramanujam et al., 2015). The relative risk of developing MS among smokers is almost twice that of never‐smokers, and patients with MS who smoke exhibit a more severe disease course and a faster disability progression rate (Correale & Farez, 2015; Fragoso, 2014; Healy et al., 2009; Manouchehrinia et al., 2013; Zhang et al., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Like other autoimmune disorders, MS is considered to be triggered by environmental factors in individuals with a genetic predisposition, and smoking has been considered one of the most established environmental risk factors for this illness (Mandia et al., 2014; Ramanujam et al., 2015). The relative risk of developing MS among smokers is almost twice that of never‐smokers, and patients with MS who smoke exhibit a more severe disease course and a faster disability progression rate (Correale & Farez, 2015; Fragoso, 2014; Healy et al., 2009; Manouchehrinia et al., 2013; Zhang et al., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of studies have shown that risk factors such as candidate genes [6,7],smoking [8][9][10], geographic location [11,12], viral infections [13][14][15][16][17], wheat consumption [11,18], dairy product consumption [19,20], fish intake [21], animal fat intake [21], high ultraviolet radiation [22][23][24] and Vitamin D [25][26][27] amplify the risk of developing MS or its progression. They might work in synchrony with other risk factors and genes, thus leading to disease onset.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking among PwMS has been shown to be associated with decreased whole brain volume and increased T2 lesion volume, increased contrast enhancing lesions, and T1 lesion volume on MRI. 15,16,18 More recent findings suggest that smoking cessation has also been associated with a significant decline in the rate of brain volume loss compared with current smokers. 19 Given the high prevalence rates of current smoking among PwMS, interventions aimed at smoking cessation may substantially improve MS-related outcomes and reduce the risk of developing smoking-related comorbidities.…”
Section: Smokingmentioning
confidence: 99%